2019
DOI: 10.1093/mnras/stz335
|View full text |Cite
|
Sign up to set email alerts
|

GMRT observations of extragalactic radio sources with steeply inverted spectra

Abstract: We report quasi-simultaneous GMRT observations of seven extragalactic radio sources at 150, 325, 610 and 1400 MHz, in an attempt to accurately define their radio continuum spectra, particularly at frequencies below the observed spectral turnover. We had previously identified these sources as candidates for a sharply inverted integrated radio spectrum whose slope is close to, or even exceeds α c = +2.5, the theoretical limit due to synchrotron self-absorption (SSA) in a source of incoherent synchrotron radiatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
(64 reference statements)
5
11
3
Order By: Relevance
“…Also, the dense environment indicated by the high optical depth would be consistent with the possibility of FFA mechanism being responsible for the sharp spectral turnover witnessed for the source J1209−2032, as inferred for GPS and CSS sources (Pihlström et al 2003;Bicknell et al 2018). A discussion on the FFA process operating in such extremely inverted sources is provided in Mhaskey et al (2019b).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Also, the dense environment indicated by the high optical depth would be consistent with the possibility of FFA mechanism being responsible for the sharp spectral turnover witnessed for the source J1209−2032, as inferred for GPS and CSS sources (Pihlström et al 2003;Bicknell et al 2018). A discussion on the FFA process operating in such extremely inverted sources is provided in Mhaskey et al (2019b).…”
Section: Discussionsupporting
confidence: 63%
“…For the source J1549+5038 Pasetto et al (2016 inferred a large (restframe) rotation measure (RM = 1400 ± 500 rad m −2 ). The available radio continuum data for J1549+5038 confirms a strong flux variability at centimetre wavelengths, as cited in Mhaskey et al (2019b).…”
Section: J1209−2032 and J1549+5038supporting
confidence: 63%
“…We find a spectral index difference of ∆α = α 2 − α 1 = 0.45 ± 0.1, which is less than the theoretical limit imposed by pure synchrotron self-absorption (Mhaskey et al 2019). This indicates that other absorption processes may also influence the flat spectrum radio SED, such as free-free absorption (Kameno et al 2005;Tingay & de Kool 2003).…”
Section: Flat Spectrum Sourcescontrasting
confidence: 57%
“…Our sources have optically thick spectral index constraints that are consistent with SSA, though improved spectral coverage at low frequencies (<1 GHz) will ultimately be needed (Callingham et al 2015;Collier et al 2018;Keim et al 2019;Mhaskey et al 2019aMhaskey et al , 2019b. The identification of FFA associated with any of the newly radio-loud AGNs in our sample would be of particular interest in the context of galaxy evolution since simulations have shown that it may arise from jet−ISM interactions (Bicknell et al 1997(Bicknell et al , 2018.…”
Section: Radio Color-color Diagrammentioning
confidence: 66%
“…In a future study, we will incorporate new data from forthcoming VLA and Giant Metre-wave Radio Telescope (GMRT) observations spanning a broader frequency range (the full contiguous frequency range of the VLA from 1 to 50 GHz and deep measurements below 1 GHz using the VLA and GMRT). This will enable a more rigorous radio SED modeling analysis that will allow us to test whether SSA or FFA is responsible for the observed spectral curvature (Mhaskey et al 2019a(Mhaskey et al , 2019b.…”
Section: Radio Sed Modelingmentioning
confidence: 99%